MARKETING STRATEGY OF LAGUNDI SEAWEED PROCESSED PRODUCTS AND ITS IMPACT ON COMMUNITY WELFARE IN LIYA MAWI VILLAGE FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS - Hestia; Sitti Rahma Gurudin; La Ode Aslan (Jurnal Dinamika Ekonomi Syariah, 2025)
The objectives of this study are: (1) To examine the marketing strategy of Lagundi seaweed processed products in Liya Mawi Village, Wakatobi Regency; (2) To analyze the welfare of the community in Liya Mawi Village, Wakatobi Regency; and (3) To understand how the marketing strategy of Lagundi seaweed processed products contributes to community welfare based on Islamic economic principles. This research uses a qualitative approach. The study was conducted in Liya Mawi Village, Wakatobi Regency, with the marketing strategy of Lagundi seaweed products and its relation to community welfare as the main focus.The findings of this research indicate that: (1) The marketing strategy of Lagundi seaweed processed products involves a series of steps and tactics based on the marketing mix—product, price, place, and promotion—to promote and sell the products; (2) The growth of productive economic activities such as seaweed processing has contributed to improving the community’s welfare in several aspects, including education,health, clothing, food, and housing; (3) The business activities of Lagundi seaweed products are carried out based on sharia economic principles that emphasize justice, balance, and transparency